STRATEGI PEMASARAN CAFE NYOMAN SEAFOOD CAFE JIMBARAN-BALI - I Made Subagiada (Jurnal Manajemen dan Bisnis, 2013)
of Nyoman Cafe in Jimbaran Beach, a new product components Balitourism should be maintained, for the continuation of all the problems that arise related tomarketing in order to overcome, to create profitable customer satisfaction on an ongoingbasis and to further increase the number of visitors. This study aims to assess the strengthsand weaknesses of internal factors, opportunities and threats from Nyoman Cafe externalfactor in Jimbaran beach and then formulate a marketing strategy which outlined the variousmarketing programs. Data collected by observation, questionnaires and documentationdistribution and then using 7P (marketing mix) of product, price, place, promotion, people,process, physical evidence. Sample retrieval technique using purposive sampling.The results of research done on elements such as segmenting strategy conducted inthe Nyoman Café on every tourist. Targeting is a way undifferentiated marketing premise.Created by positioning the competitive price while still maintaining the quality of productsand services. produce a strategy that is strategies greater cooperation with Travel agents,hotels and local communities, strategy of developing new products and increasedpromotional strategy, Strategies to create differentiation strategies (typical) on the NyomanCafe, strategy to maintain and improve the quality of services and products offered andimprove the quality of human resources strategy.Based on the results of the discussion can be given advice on marketing strategies inthe Nyoman Café Muaya Jimbaran Beach, Bali. The proposal is to reduce the price of foodand drinks at Cafe Nyoman, improve the quality of human resources in a way to financekhursus employees with foreign language, improve hygiene furniture, equipment andcleanliness Nyoman Cafe, complete equipment and facilities at the Nyoman Cafe for smooth,and improve safety at the Nyoman Cafe.Keywords : Marketing Strategy and Cafe Seafood